2022
DOI: 10.1097/rli.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Iodinated Contrast Media Administration in Coronary CT Angiography on a Clinical Photon-Counting Detector CT System

Abstract: PurposeThe aim of this study was to evaluate strategies to reduce contrast media volumes for coronary computed tomography (CT) angiography on a clinical first-generation dual-source photon-counting detector (PCD)-CT system using a dynamic circulation phantom.Materials and MethodsCoronary CT angiograph is an established method for the assessment of coronary artery disease that relies on the administration of iodinated contrast media. Reduction of contrast media volumes while maintaining diagnostic image quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 33 publications
(80 reference statements)
0
25
0
1
Order By: Relevance
“…Just as in DECT, VMIs can be generated from PCD-CT 23,26,71,110,111 . In addition to tube potential and tube current, PCD-CT systems require the selection of additional acquisition parameters, such as energy thresholds, which can further complicate clinical workflow.…”
Section: Virtual Monoenergetic Images and The Standardization Of Ct N...mentioning
confidence: 99%
“…Just as in DECT, VMIs can be generated from PCD-CT 23,26,71,110,111 . In addition to tube potential and tube current, PCD-CT systems require the selection of additional acquisition parameters, such as energy thresholds, which can further complicate clinical workflow.…”
Section: Virtual Monoenergetic Images and The Standardization Of Ct N...mentioning
confidence: 99%
“…19 Improvements in image quality with a higher CNR provide the ground for lowering the radiation dose and/or reduction of the amount of administered iodinated contrast media. 20,21 Emrich et al 22 showed in a phantom study that with use of virtual monoenergetic reconstructions at 40 keV, a sufficient CNR at a 50% reduction of contrast media dosage can be achieved. In a prospective study with 100 patients, Higashigaito et al 23 showed that the improved CNR of CT angiography with PCD-CT allows considerable contrast media reduction.…”
Section: Iterative Reconstructionmentioning
confidence: 99%
“…At low-energy, that is, 40 keV, VMI enables an increase in CT attenuation of iodine and more generally of tissue with high photoelectric absorption. This improves contrast-to-noise ratios of enhanced lesions or vessels 55,56 and decreases the iodine load for a satisfactory level of vessel opacification 57–59 . At higher energy than 70 keV, VMI enables a reduction of beam-hardening like-artifacts, thus improving the visualization of tissues surrounding high-attenuating tissues, iodinated vessels, 60 or metallic structures such as stents or prostheses 61,62 .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…This improves contrast-tonoise ratios of enhanced lesions or vessels 55,56 and decreases the iodine load for a satisfactory level of vessel opacification. [57][58][59] At higher energy than 70 keV, VMI enables a reduction of beam-hardening likeartifacts, thus improving the visualization of tissues surrounding high-attenuating tissues, iodinated vessels, 60 or metallic structures such as stents or prostheses. 61,62 In our experience, the advantages of using VMI with SPCCT rely in the combination of all the technical benefits, that is, an improved spatial resolution, an improved discrimination between photoelectric and Compton effects, as well as a greater dose efficiency and weighting of the low-energy photons.…”
Section: Virtual Monochromatic Imagingmentioning
confidence: 99%